Versatile 3D‐Printed Micro‐Reference Electrodes for Aqueous and Non‐Aqueous Solutions. Issue 42 (12th September 2021) - Schuett, Fabian M.; Zeller, Sven J.; Eckl, Maximilian J.; Matzik, Felix M.; Heubach, Maren‐Kathrin; Geng, Tanja; Hermann, Johannes M.; Uhl, Matthias; Kibler, Ludwig A.; Engstfeld, Albert K.; Jacob, Timo
Abstract: While numerous reference electrodes suitable for aqueous electrolytes exist, there is no well‐defined standard for non‐aqueous electrolytes. Furthermore, reference electrodes are often large and do not meet the size requirements for small cells. In this work, we present a simple method for fabricating stable 3D‐printed micro‐reference electrodes. The prints are made from polyvinylidene fluoride, which is chemically inert in strong acids, bases, and commonly used non‐aqueous solvents. We chose six different reference systems based on Ag, Cu, Zn, and Na, including three aqueous and three non‐aqueous systems to demonstrate the versatility of the approach. Subsequently, we conducted cyclic voltammetry experiments and measured the potential difference between the aqueous homemade reference electrodes and a commercial Ag/AgCl‐electrode. For the non‐aqueous reference electrodes, we chose the ferrocene redox couple as an internal standard. From these measurements, we deduced that this new class of micro‐reference electrodes is leak‐tight and shows a stable electrode potential. Abstract : The lack of stable reference electrodes (REs) for electrochemical measurements in small cell arrangements is an often‐neglected problem. Herein we present an easily applicable procedure for the assembly of stable and cheap micro‐REs, which are highly adaptable due to 3D‐printed housings; 3 aqueous and 3 non‐aqueous micro‐REs based on Ag, Cu, Zn, and Na. After fabrication, their stability and leak‐tightness are shown by electrochemical measurements.